Role of Rural Banks in the Development of Self-Help Groups - Jeevan Singh Kishnawat (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
Majority of the population of Rajasthan lives in rural areas. Before independence, debt payments were made by moneylenders and Nagar Seth. After the establishment of the Village Bank on October 2, 1975, they were entrusted with the task of disbursing village loans. Rural banks provide individual and group loans for rural development under various schemes. This includes self-help groups. In this group, the village bank plays a positive role in the development of the rural economy by collecting small savings of women and men and providing them in the form of group loans. In addition to savings, discussions on problem solving and development at the village level also started at the Self Help Group meeting. Self-help groups play an important role in empowering women. As the living standards of these groups of farmers and herdsmen improved, self-employment increased. Currently, there are two rural banks operating in Rajasthan, namely Rajasthan Marudhara Gramin Bank and Rajasthan Kshetriya Gramin Bank of Baroda. With the cooperation with the village bank in developing self-help groups at the village level, the economic and living standards have also improved by increasing the savings and living standards of the residents.